Evaluation of Public Service Performance of the Government at the Lingga Regency Tourism Office - Srinita, Geby Gita; Febrianty, Wan Jesica; Putri, Rizqi Apriani (Indonesian Tourism Journal, 2025)
The tourism sector in Lingga Regency holds significant potential as a catalyst for regional economic development, especially given its rich marine, cultural, and historical assets. However, this potential remains underutilized due to persistent issues in public service performance, particularly within the Tourism Office. The background of this research is the low effectiveness and efficiency of tourism-related public services, as evidenced by the drastic gap between strategic targets and actual outcomes most notably, the revitalization of tourist destinations, which only reached 7.03% of the planned 80% target in 2024. This study aims to evaluate the performance of public service delivery in Lingga's tourism sector using a three-dimensional model comprising input, output, and outcome dimensions. Employing a qualitative research approach, data were gathered through in-depth interviews with key officials, field observations at tourism sites, and analysis of strategic and accountability documents such as LAKIP and RPJMD. Data were analyzed using a structured coding system based on ten performance indicators, including service structure, responsiveness, stakeholder engagement, and policy alignment. The results show that although strategic plans and organizational frameworks exist, implementation is hindered by weak coordination, limited infrastructure, underdeveloped human resource capacity, and low community involvement. Promotional efforts and digital engagement are also insufficient to create a compelling tourism brand. The conclusion emphasizes the need for institutional reform through enhanced capacity building, performance-based budgeting, stakeholder collaboration, and the adoption of community-based tourism.